The 'Gaduh Sapi' Livestock-Sharing Tradition in the Lens of Islamic Economics: A Harmonization of Local Wisdom and Sharia Principles - Anjarwati, Atika; Daud; Abidin, Zaenal; Nurjali; Pitri, Alisyah; Nilfatri; Sarwono (Journal of Economics and Social Sciences (JESS), 2025)
This study explores the profit-sharing practices within the gaduh sapi (shared cattle-rearing) system prevalent in Muara Sabak Barat District, Tanjung Jabung Timur Regency, Jambi Province, from the perspective of Islamic economics. The gaduh sapi system represents a traditional form of cooperation between a capital provider (the cattle owner) and a manager (the caretaker), established orally and grounded in social trust. This research adopts a qualitative approach using a case study method to investigate the mechanisms of profit-sharing, patterns of responsibility, and the challenges inherent in the practice. The findings reveal that, while the system embodies values such as honesty and mutual cooperation, imbalances persist in terms of risk distribution, maintenance cost burdens, and weak communication between parties. The absence of written contracts and clearly defined roles poses risks of conflict and potential injustice. From an Islamic economic perspective, the practice contains elements of gharar (uncertainty) and does not fully comply with the principles of mudharabah or musyarakah, which emphasize justice, transparency, and mutual consent. Therefore, a more structured cooperation framework is needed to transform the gaduh sapi system into a just, beneficial, and sharia-compliant economic model.